Penerapan Pola Pengasuhan Positif Terhadap Perkembangan Sosial Emosional Pada Anak Usia Dini - Ardita Afiani (Childhood Education : Jurnal Pendidikan Anak Usia Dini, 2024)
This study aims to evaluate the impact of positive parenting practices on early childhood social-emotional development. This research uses the literature study method. Data analysis was conducted qualitatively using the miles and huberman analysis approach which involves three steps, namely data reduction, data presentation, and conclusion drawing or verification. The results showed that the application of positive parenting patterns significantly influenced social-emotional development in early childhood. The conclusion of this study states that the application of positive parenting patterns has a positive impact on social-emotional development in early childhood. As a suggestion, this study emphasises the need for understanding and implementation of positive parenting patterns by parents as an effort to support the optimal development of early childhood. Keywords: Positive Parenting, Social-Emotional Development